Revealed Political Favoritism: Evidence from the Allocation of State Lottery Grants in Israel - Momi Dahan; Itamar Yakir (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper offers a complementary empirical approach that might be better suited to identify the extent of political favoritism in a multi-decision-maker institution than the standard identification strategy. The typical diff-in-diff identification strategy to estimate political favoritism, which rests on a comparison of two decision makers that allocate public funds to two groups, seems inadequate in a multi-player setting due to the multiple and conflicting political interests and social affiliations. To illustrate how our approach uncovers the degree of political favoritism, we use a policy change in allocating state lottery revenues to Israeli municipalities from discretion-based allocation to rules-based allocation. We find significant political favoritism under the old regime relative to the new one toward Jewish (versus Arab) and affluent (versus less affluent) municipalities. Our results suggest that adopting rules-based allocation might be effective in coping with political favoritism.
Keywords: 330; political favoritism; grant allocation; local government; rules vs. discretion